1985
DOI: 10.1136/thx.40.6.412
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary platelet kinetics in asthma.

Abstract: Platelets produce a range of bronchoconstrictor mediators. Measurements of plasma factors have implicated platelet activation in allergic asthma, and sensitised guineapigs challenged with ovalbumin show pulmonary platelet aggregation accompanying bronchoconstriction. To investigate this further we injected autologous platelets labelled with indium 111 and red cells labelled with technetium 99m into three young volunteers with atopic asthma and three nonasthmatic volunteers and, after equilibration of platelets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…This supports data indicating platelet sequestration in the bronchial circulation of challenged atopic asthmatics [63]. These findings are, nevertheless, inconclusive, as other reports show no reduction in platelet survival time and no evident platelet sequestration in the pulmonary microvasculature [64,65]. One finding that is widely acknowledged, is the prolonged bleeding time observed in atopic subjects [66,67].…”
Section: Clinical Evidence For a Role Of Platelets In Asthmasupporting
confidence: 80%
“…This supports data indicating platelet sequestration in the bronchial circulation of challenged atopic asthmatics [63]. These findings are, nevertheless, inconclusive, as other reports show no reduction in platelet survival time and no evident platelet sequestration in the pulmonary microvasculature [64,65]. One finding that is widely acknowledged, is the prolonged bleeding time observed in atopic subjects [66,67].…”
Section: Clinical Evidence For a Role Of Platelets In Asthmasupporting
confidence: 80%
“…Impaired gas exchange due to pressure differences, insufficient surface area increased transit time of red blood cells and platelets and insufficient alveolar ventilation-perfusion results in rapid development of dyspnea during exercise, and thus limits physical capacity. [30][31][32][33] This occurs even in mild asthma. 9 In patients with asthma, increased end-expiratory lung volume, lower physical activity and a more sedentary lifestyle than healthy people of the same age are other reasons for lower exercise tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we demonstrated lowest platelet counts in peripheral blood of patients with mild persistent asthma. This is also inconclusive that other studies demonstrated platelet survival time within normal limits [28,30]. This is also inconclusive that other studies demonstrated platelet survival time within normal limits [28,30].…”
Section: Discussionmentioning
confidence: 82%